Kualitas Pelayanan Publik pada Bidang Administrasi Kependudukan di Desa Mataindaha Kecamatan Pasi Kolaga Kabupaten Muna - Wilda Isnaini; Rosman Ilato; Irawaty Igirisa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The purpose of this study is to describe the Quality of Public Services in the Population Administration Sector in Mataindaha Village, Pasi Kolaga District, Muna Regency. To do this, the researcher uses dimensions, namely; (1) tangibless (physical evidence), (2) reliability (reliability), (3) responsiveness (responsiveness), (4) assurance (assurance), and (5) empathy (attention). To do this, this study uses a qualitative descriptive method, with 10 (ten people). The data collection techniques used in this study are based on observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and data explanation. The results of the study indicate that the tangible dimension is still lacking and needs to be carefully reconsidered by village officials (2) assurance, which also needs to be improved considering that village equipment has not been able to provide timely and accurate services. While other dimensions include (3) reliability. Other dimensions include (4) responsiveness and finally (5) empathy has succeeded in helping the community and providing information about service procedures that are not yet understood by the community.